2007
DOI: 10.1038/ncpneph0362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Disease: the role of aldosterone in kidney damage and clinical benefits of its blockade

Abstract: In the past 10 years, many widely accepted concepts relating to aldosterone production and its pathogenetic role have changed. We now know that aldosterone is produced not only by the zona glomerulosa of the adrenal cortex, but also in the heart, blood vessels, kidney and brain; such extra-epithelial production occurs mainly during tissue repair. Also, increased aldosterone levels contribute to vessel inflammation, oxidative stress, endothelial dysfunction and organ damage. As such, aldosterone has a key role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 51 publications
0
48
1
Order By: Relevance
“…Clinical studies confirmed an independent effect of aldosterone in human renal disease progression despite angiotensin-converting enzyme (ACE)-inhibitor (ACEI) or angiotensin AT1 receptor blockade (ARB) treatment. 7 Aldosterone has been reported to contribute to the pathogenesis of glomerular mesangial injury, TIF and proteinuria in non-diabetic chronic kidney disease (CKD) and diabetic nephropathy. [8][9][10][11][12] Elevated plasma aldosterone levels occur in up to half of all patients on chronic ACE inhibitor or ARB therapy, possibly due to elevated potassium levels.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies confirmed an independent effect of aldosterone in human renal disease progression despite angiotensin-converting enzyme (ACE)-inhibitor (ACEI) or angiotensin AT1 receptor blockade (ARB) treatment. 7 Aldosterone has been reported to contribute to the pathogenesis of glomerular mesangial injury, TIF and proteinuria in non-diabetic chronic kidney disease (CKD) and diabetic nephropathy. [8][9][10][11][12] Elevated plasma aldosterone levels occur in up to half of all patients on chronic ACE inhibitor or ARB therapy, possibly due to elevated potassium levels.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by findings that in other organs such heart after myocardial infarction, the excessive aldosterone production is associated with harmful local effects that include generation of reactive oxygen species (ROS), endothelial dysfunction, stimulation of cell growth and proliferation, and ultimately development of fibrosis. 9 Furthermore, the intravenous infusion of aldosterone in adrenalectomized rats with renal mass ablation-a model of progressive kidney disease-abrogates the renoprotective effect of ACEi or ARB, further indicating the contribution of the hormone to kidney damage. 10 Although the molecular pathways of aldosterone-mediated renal injury have not yet been fully elucidated, they all seem to contribute to the final common pathway of renal fibrosis.…”
mentioning
confidence: 99%
“…8 Moreover, in the rat kidney, the mineralocorticoid receptor has been localized to preglomerular vasculature, mesangial cells, and fibroblasts as well as distal tubular cells of the nephron. 9 Thus, the intrarenal sites of aldosterone production and expression patterns of its receptor, together with the observation that mediators of renal disease progression promote the local synthesis of aldosterone, suggest a possible direct role of this mineralocorticoid hormone in kidney damage. This notion is supported by findings that in other organs such heart after myocardial infarction, the excessive aldosterone production is associated with harmful local effects that include generation of reactive oxygen species (ROS), endothelial dysfunction, stimulation of cell growth and proliferation, and ultimately development of fibrosis.…”
mentioning
confidence: 99%
“…Clinical and experimental works have suggested that mineralocorticoid receptor blockade may be beneficial for renal disease in diabetes. 2,3,6,7,10,11,26 In addition, a recent clinical trial concluded that adding spironolactone, an aldosterone blocker, to the maximal dose of ACEi provides greater renal protection, despite a similar effect on blood pressure and blood glucose. 2 Furthermore, experimental data suggest that the effect of aldosterone on glomerular and tubular sclerosis is independent of angiotensin II.…”
Section: Discussionmentioning
confidence: 99%